THE ROLE OF ZAKAT MAAL MANAGEMENT IN BSI MASLAHAT THROUGH POVERTY ALLEVIATION - Nadya, Prameswara Samofa; Febriyanti, Alfina; Alwyni, Farouk Abdullah (Proceeding International Seminar of Islamic Studies, 2023)
The problem in Indonesia that is very difficult to overcome or resolve is poverty, especially in various regions of provinces. There are many ways to alleviate poverty, of which is zakat by setting aside a portion of assets for eight ashnaf groups. The purpose of this research was to determine the effectiveness of zakat maal management. This research uses qualitative methods by analyzing information sourced from interviews. Continues to increase from year to year and is managed properly in a trustworthy and professional manner. the zakat maal distribution programs carried out by BSI Maslahat are in accordance with the needs of the mustahik and the financial reports on the receipt and distribution of zakat finds experience a deficit/surplus. Recommendations of this research are: it is important to collect more detailed data so that the distribution of zakat funds is not misdirected and to provide guidance and supervision of the programs that have been implemented.